Fairness perceptions regarding in-work benefits: a survey experiment - Senghaas, Monika; Osiander, Christopher; Stephan, Gesine; Struck, Olaf (International Journal of Sociology and Social Policy, 2022)
Purpose - In many countries, individuals can receive welfare support whilst simultaneously being employed. The level of earned income that welfare recipients are allowed to keep has long been a subject of debate. Core issues include whether in-work benefit regulations provide incentives for individuals to expand labour market participation and are thus also socially effective and whether the population perceives welfare benefits for individuals who earn own income as fair. This article contributes to the debate about the social legitimacy of in-work benefit regulations by shedding light on the principles guiding judgements about an adequate amount of in-work benefit receipt.
CRIS-Team WoS Importer:2022-08-26